Public Perception of Television News Coverage on the Vina Cirebon Case: A Case Study of TVOne Broadcasts in RT 006, Gunung Agung, Bandar Lampung - Daniati, Rachma; Verawati, Noning; Pienrasmi, Hanindyalaila (Indonesian Journal Publisher, 2025)
This study examines the public perception of the news coverage regarding the Vina Cirebon case aired on TVOne. The case of Vina, a 16-year-old student from Cirebon, drew widespread attention after a film titled